Lack of TRPV2 impairs thermogenesis in mouse brown adipose tissue - Sun, Wuping (EMBO Rep, 2016)
Brown adipose tissue (BAT), a major site for mammalian non‐shivering thermogenesis, could be a target for prevention and treatment of human obesity. Transient receptor potential vanilloid 2 (TRPV2), a Ca(2+)‐permeable non‐selective cation channel, plays vital roles in the regulation of various cellular functions. Here, we show that TRPV2 is expressed in brown adipocytes and that mRNA levels of thermogenic genes are reduced in both cultured brown adipocytes and BAT from TRPV2 knockout (TRPV2KO) mice. The induction of thermogenic genes in response to β‐adrenergic receptor stimulation is also decreased in TRPV2KO brown adipocytes and suppressed by reduced intracellular Ca(2+) concentrations in wild‐type brown adipocytes. In addition, TRPV2KO mice have more white adipose tissue and larger brown adipocytes and show cold intolerance, and lower BAT temperature increases in response to β‐adrenergic receptor stimulation. Furthermore, TRPV2KO mice have increased body weight and fat upon high‐fat‐diet treatment. Based on these findings, we conclude that TRPV2 has a role in BAT thermogenesis and could be a target for human obesity therapy.